From Banks to Apps: How Fintech Lending is Reshaping Financial Institutions - zuchroh, imama; Muniroh, Muniroh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The emergence of financial technology has fundamentally transformed the traditional lending landscape, challenging centuries-old banking paradigms and creating new competitive dynamics within the financial services sector. This qualitative descriptive study examines how fintech lending platforms are reshaping financial institutions across global markets, analyzing the multidimensional impact on traditional banks, credit unions, and other financial intermediaries. Through systematic analysis of industry developments, regulatory changes, and institutional responses from 2015 to 2025, this research explores the comprehensive transformation occurring within the financial services ecosystem. The study reveals that fintech lending has catalyzed significant changes in operational models, customer engagement strategies, risk assessment methodologies, and competitive positioning of traditional financial institutions. The research demonstrates that rather than merely displacing traditional banks, fintech lending has forced a fundamental reimagining of how financial services are conceived, delivered, and regulated. Key findings indicate that successful financial institutions are those that have embraced hybrid approaches, combining traditional banking strengths with fintech innovations to create enhanced value propositions for their customers. The study also reveals significant variations in adaptation strategies across different geographic regions and institutional sizes, with larger banks generally having more resources to invest in transformation initiatives while smaller institutions often pursue partnership strategies. The research concludes that the future of financial services will be characterized by ecosystem-based approaches where traditional boundaries between banks and technology companies become increasingly blurred, requiring new regulatory frameworks and business models to address emerging challenges and opportunities in the digital financial landscape.